(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
A congenital coronary pathology described as a segment of coronary artery which courses through the myocardial wall beneath the muscle bridge is myocardial bridging. Although the myocardial bridging prognosis is benign, in medical literature have been also reported as sudden death. A 29-year-old male was died suddenly with the history of difficulty in breathing before death. The left anterior descending coronary artery was detected embedded deeply in the myocardium 1.8 cm from its coronary ostial origin. Also found anterior wall healed myocardial infarction. We analyzed sudden death case occurred because of myocardial bridging and the pathophysiological mechanisms in the light of medico-legal literature.